PENGARUH BUDAYA TRI HITA KARANA TERHADAP PENGGUNAAN SISTEM INFORMASI AKUNTANSI DIMEDIASI PERSEPSI KEGUNAAN DAN PERSEPSI KEMUDAHAN PENGGUNAAN - Suardikha, I Made Sadha (UI Scholars Hub, 2013)
This study aims to examine and analyze the direct influence of THK culture, perceived usefulness, and perceived ease of use to the use of the AIS; and indirect influence of THK culture on the use of AIS are mediated perceived usefulness and perceived ease of use. This study looked at 80 samples of LPD in Bali. Required data collected by the survey using a list of questions. Data that has been collected analyzed using analysis tools PLS Smart 2.0 M3. The test results showed that THK culture influences perceiveved usefulness, perceived ease of use, and the use of SIA. Perceived usefulness and perceived ease of use affect the use of SIA. Similarly, THK culture influence of the uses of AIS mediated perceived of usefulness and perceived ease of use.